Enhancing the Sensitivity of Percolative Graphene Films for Flexible and Transparent Pressure Sensor Arrays. (9th May 2016) - Chen, Zhuo; Ming, Tian; Goulamaly, Mahomed Mehdi; Yao, Heming; Nezich, Daniel; Hempel, Marek; Hofmann, Mario; Kong, Jing
Abstract : Flexible and transparent pressure sensor arrays can find applications in many places such as touch panels, artificial skin, or human motion detection. However, conventional strain gauges are rigid and opaque and are not suitable for such applications. Graphene‐based percolative strain gauges can overcome these challenges but currently are still in the infancy of their development. In this work, the performance of graphene‐based percolative strain gauges is investigated and guidelines to improve the durability and sensitivity of graphene films as sensing elements are developed. It is found that the gauge factor depends on the initial resistance of the graphene film. For the same film resistance, it is found that graphene flake size and film morphology also play a role in determining the gauge factor. Increasing the flake–flake resistance through assembly of surfactant molecules between graphene flakes provides an additional route to enhance the gauge factor. Furthermore, encapsulating the percolative film in micrometer‐thin Poly(methyl methacrylate) does not disrupt the sensing process but significantly improves the sensor's durability. Finally, thus enhanced graphene strain gauges are integrated into flexible and transparent pressure sensor arrays that exhibit high reproducibility and sensitivity. Abstract : The performance of graphene‐based percolative strain gauges is investigated and guidelines to improve the durability and sensitivity of graphene films as sensing elements are developed. The enhanced graphene strain gauges are encapsulated in micrometer‐thin Poly(methyl methacrylate) (PMMA) and integrated into flexible and transparent pressure sensor arrays that exhibit high reproducibility and sensitivity.